NILAI-NILAI MORAL DALAM CERPEN SHINYUU KARYA SATO KOYO - Priyono, Anto; Mulyadi, Budi; Hastuti, Nur (Japanese Literature, 2016)
The sequence of this thesis are: first the writer collects the references and analyzes the data. Then, she obtained the data from Anthology of Japanese children's literature's book. The problems that will be studied in this thesis are intrinsic, extrinsic elements and the moral values contained in Sato Shinyuu Koyo's short story. This study uses structural method. The method is used to analyze the intrinsic and extrinsic elements that lead to moral values of the story. It makes the writer easier to analyze the moral values of story. The intrinsic elements that will be discussed in this thesis are theme, character, plot, setting, point of view, and the message of story. And the extrinsic elements that will be analyzed is the author's environment.